INTEGRATION OF CUSTOMARY LAW IN THE PRINCIPLE OF LEGALITY TOWARDS A JUST INDONESIAN CRIMINAL LAW SYSTEM - Tonnes Gultom; Henry Aspan; Muhammad Arif Sahlepi (PT. Sinergi Legal Publisher, 2025)
The principle of legality is the main pillar in criminal law which functions to guarantee legal certainty and protect human rights from arbitrary actions. In the Indonesian criminal law system, this principle is reflected in Article 1 paragraph (1) of the Criminal Code which states that no act can be punished except based on previously existing written legal provisions. However, the application of the principle of legality which is too positivistic and narrow is considered less relevant in a pluralistic Indonesian society which still upholds customary law as part of living social norms. This thesis aims to reconstruct the principle of legality in the Criminal Code so that it can accommodate living legal values ​​in society (living law) without ignoring the principles of the rule of law and protection of human rights. The method used is a juridical-normative research with a historical, conceptual, and comparative legal approach. The results of the study show that the recognition of customary law in the criminal system has obtained constitutional legitimacy through Article 18B paragraph (2) of the 1945 Constitution and legal support in the 2022 Criminal Code Bill. The proposed reconstruction of the legality principle emphasizes the importance of a balance between written law and local values, through strict verification mechanisms, limitations on sanctions, and strengthening the capacity of law enforcement officers to understand legal pluralism. Thus, this reconstruction is expected to be able to create a national criminal law system that is more contextual, fair, and in accordance with the identity of the Indonesian nation.